Design of Microcontroller Programming Learning KIT Using Scratch for Arduino - Yulisman S.Kom; Uci Rahmalisa (Universitas Islam Kuantan Singingi, 2021)
Based on the results of the researcher's observations, the competence of students' skills in the subjects of Microprocessors and Microcontrollers is still lacking. This is due to the fact that the current learning method is still using the conventional method, and still using conventional program code writing model. It is difficult to understand for students who are beginners in the field of programming. The purpose of this research is to produce Learning KIT products to facilitate learning activities of Microcontroller programming with Plug and Play system, in writing program code was made easy with simply compiling instructions in the form of block puzzles. It can make easy for the beginner to understand programming logic and algorithms. The method steps taken refer to prototyping method, it aims to get an overview of the tool’s designed and built to be shown to the user. The evaluation prototype will be used as a reference to make a tool as the final product as the output of this research.